Climate and topographic controls on simulated pasture production in a semiarid Mediterranean watershed with scattered tree cover - Lozano-Parra, J; Maneta, M P; Schnabel, S (HYDROLOGY AND EARTH SYSTEM SCIENCES, 2014)
Natural grasses in semiarid rangelands constitute an effective protection against soil erosion and degradation, are a source of natural food for livestock and play a critical role in the hydrologic cycle by contributing to the uptake and transpiration of water. However, natural pastures are threatened by land abandonment and the consequent encroachment of shrubs and trees as well as by changing climatic conditions. In spite of their ecological and economic importance, the spatiotemporal variations of pasture production at the decadal-century scales over whole watersheds are poorly known. We used a physically based, spatially distributed ecohydrologic model applied to a 99.5 ha semiarid watershed in western Spain to investigate the sensitivity of pasture production to climate variability. The ecohydrologic model was run using a 300-year-long synthetic daily climate data set generated using a stochastic weather generator. The data set reproduced the range of climatic variations observed under the current climate. Results indicated that variation of pasture production largely depended on factors that also determined the availability of soil moisture such as the temporal distribution of precipitation, topography, and tree canopy cover. The latter is negatively related with production, reflecting the importance of rainfall and light interception, as well as water consumption by trees. Valley bottoms and flat areas in the lower parts of the catchment are characterized by higher pasture production but more interannual variability. A quantitative assessment of the quality of the simulations showed that ecohydrologic models are a valuable tool to investigate long-term (century scale) water and energy fluxes, as well as vegetation dynamics, in semiarid rangelands.
APS
Keywords: degradation; ecohydrology; Grasslands; pasture production; semiarid rangelands; soil erosion

Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater - Pinto, Clara A.; Nadezhdina, Nadezhda; David, Jorge S; Kurz-Besson, Cathy; Caldeira, Maria C; Henriques, Manuel O; Monteiro, Fernando G; Pereira, João S; David, Teresa S (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.
Keywords: Cork oak; ecohydrology; sap flow radial profile; tree water sources; tree water use; water balance

Long-term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - LIMOUSIN, J. M.; Rambal, S.; OURCIVAL, J. M.; Rocheteau, A.; JOFFRE, R.; RODRIGUEZ-CORTINA, R. (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4-year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well-watered periods. Despite a tight stomatal control over transpiration, whole-tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought; ecohydrology; Hydraulic conductance; leaf area index; leaf water potential; Mediterranean evergreen forest; Quercus ilex; throughfall exclusion; Transpiration

What limits evaporation from Mediterranean oak woodlands – The supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? - Baldocchi, Dennis D.; Xu, Liukang (Advances in Water Resources, 2007)
The prediction of evaporation from Mediterranean woodland ecosystems is complicated by an array of climate, soil and plant factors. To provide a mechanistic and process-oriented understanding, we evaluate theoretical and experimental information on water loss of Mediterranean oaks at three scales, the leaf, tree and woodland. We use this knowledge to address: what limits evaporation from Mediterranean oak woodlands – the supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? The Mediterranean climate is highly seasonal with wet winters and hot, dry summers. Consequently, available sunlight is in surplus, causing potential evaporation to far exceed available rainfall on an annual basis. Because the amount of precipitation to support woody plants is marginal, Mediterranean oaks must meet their limited water supply by a variety of means. They do so by: (1) constraining the leaf area index of the landscape by establishing a canopy with widely spaced trees; (2) reducing the size of individual leaves; (3) by adopting physiological characteristics that meter the use of water (e.g. regulating stomatal, leaf nitrogen/photosynthetic capacity and/or hydraulic conductance); (4), by tapping deep supplies of water in the soil; (5) and/or by adopting a deciduous life form, which reduces the time interval that the vegetation transpires.
Keywords: ecohydrology; evaporation; quercus douglasii; savanna; Transpiration

How plant functional-type, weather, seasonal drought, and soil physical properties alter water and energy fluxes of an oak–grass savanna and an annual grassland - Baldocchi, Dennis D.; Xu, Liukang; Kiang, Nancy (Agricultural and Forest Meteorology, 2004)
Savannas and open grasslands often co-exist in semi-arid regions. Questions that remain unanswered and are of interest to biometeorologists include: how do these contrasting landscapes affect the exchanges of energy on seasonal and annual time scales; and, do biophysical constraints imposed by water supply and water demand affect whether the land is occupied by open grasslands or savanna? To address these questions, and others, we examine how a number of abiotic, biotic and edaphic factors modulate water and energy ﬂux densities over an oak–grass savanna and an annual grassland that coexist in the same climate but on soils with different hydraulic properties. The net radiation balance was greater over the oak woodland than the grassland, despite the fact that both canopies received similar sums of incoming short and long wave radiation. The lower albedo and lower radiative surface temperature of the transpiring woodland caused it to intercept and retain more long and shortwave energy over the course of the year, and particularly during the summer dry period. The partitioning of available energy into sensible and latent heat exchanged over the two canopies differed markedly. The annual sum of sensible heat exchange over the woodland was 40% greater than that over the grassland (2.05 GJ m−2 per year versus 1.46 GJ m−2 per year). With regards to evaporation, the oak woodland evaporated about 380 mm of water per year and the grassland evaporated about 300 mm per year. Differences in available energy, canopy roughness, the timing of physiological functioning, water holding capacity of the soil and rooting depth of the vegetation explained the observed differences in sensible and latent heat exchange of the contrasting vegetation surfaces. The response of canopy evaporation to diminishing soil moisture was quantiﬁed by comparing normalized evaporation rates (in terms of equilibrium evaporation) with soil water potential and volumetric water content measurements. When soil moisture was ample normalized values of latent heat ﬂux density were greater for the grassland (1.1–1.2) than for the oak savanna (0.7–0.8) and independent of moisture content. Normalized rates of evaporation over the grassland declined as volumetric water content dropped below 0.15 m3 m−3 , which corresponded with a soil water potential of −1.5 MPa. The grassland senesced and quit transpiring when the volumetric water content of the soil dropped below −2.0 MPa. The oak trees, on the other hand, were able to transpire, albeit at low rates, under very dry soil conditions (soil water potentials below −4.0 MPa). The trees were able to endure such low water potentials and maintain basal levels of metabolism because ecological forcings kept the tree density and leaf area index of the woodland low, physiological factors forced the stomata to close progressively and the trees were able to tap deeper water sources (below 0.6 m) than the grasses.
Keywords: Biosphere–atmosphere interactions; ecohydrology; evaporation

How plant functional-type, weather, seasonal drought, and soil physical properties alter water and energy fluxes of an oak–grass savanna and an annual grassland - Baldocchi, Dennis D; Xu, Liukang; Kiang, Nancy (Agricultural and Forest Meteorology, 2004)
Savannas and open grasslands often co-exist in semi-arid regions. Questions that remain unanswered and are of interest to biometeorologists include: how do these contrasting landscapes affect the exchanges of energy on seasonal and annual time scales; and, do biophysical constraints imposed by water supply and water demand affect whether the land is occupied by open grasslands or savanna? To address these questions, and others, we examine how a number of abiotic, biotic and edaphic factors modulate water and energy ﬂux densities over an oak–grass savanna and an annual grassland that coexist in the same climate but on soils with different hydraulic properties. The net radiation balance was greater over the oak woodland than the grassland, despite the fact that both canopies received similar sums of incoming short and long wave radiation. The lower albedo and lower radiative surface temperature of the transpiring woodland caused it to intercept and retain more long and shortwave energy over the course of the year, and particularly during the summer dry period. The partitioning of available energy into sensible and latent heat exchanged over the two canopies differed markedly. The annual sum of sensible heat exchange over the woodland was 40% greater than that over the grassland (2.05 GJ m−2 per year versus 1.46 GJ m−2 per year). With regards to evaporation, the oak woodland evaporated about 380 mm of water per year and the grassland evaporated about 300 mm per year. Differences in available energy, canopy roughness, the timing of physiological functioning, water holding capacity of the soil and rooting depth of the vegetation explained the observed differences in sensible and latent heat exchange of the contrasting vegetation surfaces. The response of canopy evaporation to diminishing soil moisture was quantiﬁed by comparing normalized evaporation rates (in terms of equilibrium evaporation) with soil water potential and volumetric water content measurements. When soil moisture was ample normalized values of latent heat ﬂux density were greater for the grassland (1.1–1.2) than for the oak savanna (0.7–0.8) and independent of moisture content. Normalized rates of evaporation over the grassland declined as volumetric water content dropped below 0.15 m3 m−3 , which corresponded with a soil water potential of −1.5 MPa. The grassland senesced and quit transpiring when the volumetric water content of the soil dropped below −2.0 MPa. The oak trees, on the other hand, were able to transpire, albeit at low rates, under very dry soil conditions (soil water potentials below −4.0 MPa). The trees were able to endure such low water potentials and maintain basal levels of metabolism because ecological forcings kept the tree density and leaf area index of the woodland low, physiological factors forced the stomata to close progressively and the trees were able to tap deeper water sources (below 0.6 m) than the grasses.
Keywords: Biosphere–atmosphere interactions; ecohydrology; evaporation